Pengaruh Penerapan Model Pembelajaran Project Based Learning dan Prestasi Belajar Praktik Kerja Industri Terhadap Minat Berwirausaha Siswa Tata Kecantikan Kulit dan Rambut di SMK Negeri 7 Jember : Penelitian - Siti Anisa; Khusnul Khotimah; Arif Hidayatullah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Learning is a process of developing the potential and character building of each student as a result of the synergy between education that takes place in schools, family and community. This process provides opportunities for students to develop their potential into abilities that are increasingly increasing in attitudes (spiritual and social), knowledge, and skills needed for their own life and social life in general, as a nation, and contribute to the welfare of life. mankind with entrepreneurial determination. In order to realize an effective and efficient learning process, each education unit applies learning methods and prepares learning programs. Project Based Learning learning methods are known to be effective in increasing the knowledge and skills of students in schools. Meanwhile, learning programs can take place in schools, in the family environment, and in the community. Learning programs specifically programmed to be held in the community include, among others, Industrial Work Practices. The Internship Program is jointly arranged between schools and the community in order to meet the needs of students, as well as a vehicle for contributing to the world of work towards efforts to develop education in SMK.